Availability of data on diets in South Asia: A data availability assessment for Bangladesh, India, Nepal, and Pakistan - Scott, Samuel P.; Neupane, Sumanta; Menon, Purnima; Kishore, Avinash; Krupnik, Timothy J. (International Food Policy Research Institute, 2022)
ABOUT THIS NOTE This research note presents findings on the availability of diet-related data in publicly available population-based surveys conducted in Bangladesh, India, Nepal, and Pakistan in the last decade. It is intended to be used by researchers and policymakers to understand the data landscape and identify measurement priorities for future surveys. KEY FINDINGS • Data on diets for older children and adolescents are captured less frequently than for younger children and women of reproductive age. • Data are mostly available on food group consumption and for infants and young children; data on consumption of unhealthy foods is poor. • Few surveys capture quantity of foods consumed; estimating nutrient intake from population-based surveys is therefore not possible. • Only Bangladesh currently has large-scale publicly available and repeated rounds of data on dietary intakes for multiple age groups. • Dietary data are essential to shape public policy on nutrition; financial and technical investments are needed to scale up data availability in South Asia.